Pengaruh Jarak Tanam terhadap Laju Pertumbuhan Rumput Laut (Kappahycus alvarezii) dengan Metode Lepas Dasar - Fernando; Henky Irawan; Rika Wulandari (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2021)
There are several factors that become obstacles to the sustainability of cultivation, one of which is the growth factor. Growth is closely related to spacing and methods. This study aims to determine the optimal Spacing for the Growth Rate of K. alvarezii Using the Off-bottom Method. This research was conducted on November 1, 2020 to December 16, 2020 for 45 days with an acclimatization period of 3 days in Berakit Village, Teluk Sebong District, Bintan Regency, Riau Islands Province. The method used was experimental with a completely randomized design (CRD) with 5 treatments and 3 replications. Where A: 10 cm spacing, B: 15 cm spacing, C: 20 cm spacing, D: 25 cm spacing and E: 30 cm spacing. Data analysis using ANOVA test of variance showed a specific growth rate of 6.36±0.006 %/day), the absolute weight of K. alvarezii was 267.83±0.25 g. and absolute growth of K. alvarezii 167.83±0.25 g. The results obtained indicate that treatment D is the best treatment for growth.